Preliminary Evaluation of a Needle-Free Sensor-Based Device for Blood Glucose Measurement in Patients with Type 2 Diabetes Mellitus - Arwani Arwani; Budi Widiyanto; Sugih Wijayati; Sunarto Sunarto; Afifah Salsabila (Universitas Muhammadiyah Semarang, 2026)
Type 2 diabetes mellitus is a major public health problem with a continuously increasing prevalence, requiring accurate and continuous blood glucose monitoring. Venous blood glucose measurement using enzymatic methods remains the clinical gold standard; however, it is invasive and less practical for routine monitoring. Recent advances in sensor technology provide opportunities to develop more practical and user-friendly glucose monitoring devices. This preliminary pilot study aimed to develop and validate a needle-free sensor-based device for blood glucose monitoring and to evaluate the agreement of its measurement results with venous blood glucose examination using enzymatic methods as the reference standard. This study employed a research and development approach. The initial stage involved designing and developing a prototype sensor that monitors blood glucose without a needle. Device validation was conducted by experts to assess technical performance, safety, and usability. Subsequently, a pilot measurement of random blood glucose levels was performed among 25 patients with type 2 diabetes mellitus in a primary healthcare setting, and the measurement results were compared with venous blood glucose values obtained using enzymatic methods. The validation results indicated that the device was technically feasible, safe to use, and easy to operate. Pilot testing demonstrated that the sensor-based device produced blood glucose measurements comparable to those from the reference method (Wilcoxon Signed Ranks Test: Z = 0.000, p = 1.000), providing preliminary evidence of statistical similarity. However, further refinement is required, particularly in the interpretation and display of measurement results. These findings represent initial proof-of-concept for the device as an alternative tool for blood glucose monitoring, especially in primary healthcare settings and for patient self-monitoring. Comprehensive studies with larger, more diverse samples and advanced clinical agreement analyses (Bland-Altman plots, and MARD) are needed to confirm clinical accuracy and reliability.